Islamisasi dalam Tradisi Lisas Kasus di Sulawesi - Ghulam Gazy Prima; Zahrotul Mardiyah; Aulia Ismail; Ahmad Fikri Subarkah (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The process of Islamization in Sulawesi is an important part of the cultural and religious history of the region. Islamization not only played a role in religious change, but also involved acculturation through strong oral traditions among local communities, such as the Bugis, Makassar, and Mandar. Oral traditions including poetry, fables, proverbs, and traditional rituals were used as the main media for spreading Islamic teachings. With the arrival of Islam in the 15th and 16th centuries, Islamic values ​​were combined with local customs such as siri’ and pangadereng. The role of the nobility and ulama was very important in spreading Islamic teachings through familiar cultural narratives. In addition, traditional performing arts such as kacapi and pakarena became a means of spreading Islamic values ​​in a form that was easily accepted by the community. This article highlights how oral traditions played a role as a tool for Islamization in Sulawesi, as well as the challenges faced in maintaining these traditions in the modern era.